AWARENESS OF STOCK MARKET AMONG STUDENTS OF DEPARTMENT OF ACCOUNTANCY AND FINANCE OF S.N.D.T. UNIVERSITY AFFILIATED COLLEGES WITH REFERENCE TO MUMBAI (International Journal of Food and Nutritional Sciences, 2022)
The stock market provides a well-organized forum for buyers and sellers to trade shares. This research aims to assess students' awareness and preferences for investing in the stock market. The study relied on primary data for its findings. This study aims to increase investor awareness and confidence in the stock market. This research aims to assess students' investing awareness. The research aims to identify students' investment interests and reasons for not engaging in the share market. The research aims to assess student satisfaction with share market investments. In this research we have collected the data of 188 students and out of 182 students data will be considered. In this data we have used Chi-square test (the statistical tool) to test the Hypothesis. And The report concludes with limitations and recommendations for future studies to improve their findings.